2014
DOI: 10.1016/j.chembiol.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the 4-Methyloxazoline-Containing Nonribosomal Peptides, JBIR-34 and -35, in Streptomyces sp. Sp080513GE-23

Abstract: JBIR-34 and -35 produced by Streptomyces sp. Sp080513GE-23 are nonribosomal peptides that possess an unusual 4-methyloxazoline moiety. Through draft genome sequencing, cosmid cloning, and gene disruption, the JBIR-34 and -35 biosynthesis gene cluster (fmo cluster) was identified; it encodes 20 proteins including five nonribosomal peptide synthetases (NRPSs). Disruption of one of these NRPS genes (fmoA3) resulted in no JBIR-34 and -35 production and accumulation of 6-chloro-4-hydroxyindole-3-carboxylic acid. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 45 publications
2
65
0
1
Order By: Relevance
“…Tambromycin’s distinguishing features are a hydroxylated and chlorinated indole, a methyl-oxazoline, and 2-methyl-serine, substructures also found in JBIR-34/35 ( Figure 2 A). 10 However, an unusual pyrrolidine-containing amino acid was found upon complete structural elucidation of tambromycin by NMR, also recently reported by Izumikawa et al under the name JBIR-126. 11 Here we report the absolute stereochemistry of the tambroline monomer, the structures of tambromycin and two of its analogues, and the biosynthetic gene cluster for the compound, shown to be expressed in nine different strains.…”
Section: Introductionmentioning
confidence: 70%
“…Tambromycin’s distinguishing features are a hydroxylated and chlorinated indole, a methyl-oxazoline, and 2-methyl-serine, substructures also found in JBIR-34/35 ( Figure 2 A). 10 However, an unusual pyrrolidine-containing amino acid was found upon complete structural elucidation of tambromycin by NMR, also recently reported by Izumikawa et al under the name JBIR-126. 11 Here we report the absolute stereochemistry of the tambroline monomer, the structures of tambromycin and two of its analogues, and the biosynthetic gene cluster for the compound, shown to be expressed in nine different strains.…”
Section: Introductionmentioning
confidence: 70%
“…The established methyl oxazoline residue was also supported by comparison of the chemical shifts with those of JBIR-34. 8,9 The connectivity among these four units was established by the 1 H-13 C long-range couplings from H-2 to C-1 0 , from the a-methine proton H-2 00 and the amide proton 2 00 -NH to the amide carbonyl carbon C-5 0 , from the a-methine proton H-2 00 and the amide proton 2 000 -NH to an amide carbonyl carbon C-1 00 (d C 167.6). Finally, according to the molecular formula and the 13 C chemical shift of C-6, a chlorine atom was introduced at C-6.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%
“…8 The unique structures of JBIR-34 and -35 have been biosynthesized by a novel NRPS gene resided in Sp080513GE-23. 9 Biosynthetic studies of compounds 1-3 will be reported elsewhere. …”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…229 An example of a two-step transformation of a PCP-bound amino acid has been suggested to occur in the biosynthesis of the cyclic peptides JBIR-34 and JBIR-35. 230 In this pathway, the di-domain NRPS module FmoA1 presents a tryptophan residue (or chlorinated derivative) to the P450 FmoC, which performs two oxidation reactions; hydroxylation of the indole ring as well as b-hydroxylation.…”
mentioning
confidence: 99%